A bifunctional immunosensor based on osmium nano-hydrangeas as a catalytic chromogenic and tinctorial signal output for folic acid detection. Issue 1 (25th November 2021) - Pan, Junkang; He, Qiyi; Lao, Zhiting; Zou, Yikui; Su, Jingyi; Li, Qinglan; Chen, Zekai; Cui, Xiping; Cai, Yanfei; Zhao, Suqing
Abstract : Schematic of the bifunctional immunosensor based on osmium nano-hydrangeas as a catalytic chromogenic and tinctorial signal output for folic acid detection. Abstract : As a neglected member of the platinum group elements, osmium, the metal with the highest density in the earth, is very suitable for the preparation of a peroxidase with high catalytic activity and stability, and can also be associated with the development of a sensor. In this study, we accessed Os nano-hydrangeas (OsNHs) with one-pot synthesis and utilized them in a bifunctional immunosensor that can present both catalytic chromogenic and tinctorial signal for nanozyme-linked immunosorbent assay (NLISA) and lateral flow immunoassay (LFIA) for use in folic acid (FA) detection. In the OsNHs-NLISA, the linear range is from 9.42 to 167.53 ng mL −1 . The limit of detection (LOD) is 4.03 ng mL −1 and the IC50 value is 39.73 ng mL −1 . In OsNHs-LFIA, the visual cut-off value and limit of detection (v-LOD) are 100 ng mL −1 and 0.01 ng mL −1, respectively. Additionally, the outcome from the specificity and spiked sample analysis offered recovery from the spiked milk powder sample ranging from 93.9 to 103.6% with a coefficient of variation under 4.9%, compared with UPLC-MS/MS for a correlation of R 2 = 0.999 and admirable validation. The promising application of the OsNHs can also be used in other bioprobes, and this bifunctional immunosensor analysis mode is suitable for diversified analytes.